ABCB1 and ABCC1 single-nucleotide polymorphisms in patients treated with clozapine - Piatkov I; Caetano D; Assur Y; Lau SL; Jones T; Boyages SC; McLean M (Dove Medical Press, 2017)
Irina Piatkov, Dorgival Caetano, Yolinda Assur, Sue Lynn Lau, Trudi Jones, Steven C Boyages, Mark McLean University Clinic and Research Centre Blacktown, Western Sydney University, Western Sydney Local Health District, Blacktown, NSW, Australia Abstract: Clozapine (CZ) has superior efficacy to other antipsychotic agents in the treatment of schizophrenia and has been extensively used in clinical practice. ATP-binding cassette (ABC) transporter proteins are responsible for the distribution of various molecules as well as drugs across extracellular and intracellular membranes, including the blood–brain barrier. Genetic variations in these proteins can account for differences in treatment response. We investigated the influence of ABCB1 rs1045642 and ABCC1 rs212090 single-nucleotide polymorphisms (SNPs) on CZ serum level, clinical outcome, and changes in body mass index (BMI) in the first year of CZ treatment. These polymorphisms influenced baseline BMI in males (p=0.009 and 0.054, B1 and C1, respectively), changes in BMI in males after 3 (p=0.026, ABCB1) and 12 months (p=0.022, ABCC1) of CZ treatment, and level of diastolic pressure (p=0.002 and 0.051, respectively). The combination of ABCB1 + ABCC1 homozygote SNPs was associated with increased CZ and norclozapine serum levels (p=0.054 and 0.010, respectively). ABC transporter SNPs could be potential biomarkers for CZ-induced weight gain and cardiovascular complications. Further pharmacogenetic research is warranted to help clinicians with their treatment decision, including concomitant use of drugs and prevention of side effects. Keywords: ABC transporters, weight gain, blood pressure, rs1045642, rs212090